PENGARUH MEDIA PEMBELAJARAN BERBASIS VIDEO YOUTUBE TERHADAP MOTIVASI BELAJAR IPS SISWA SEKOLAH DASAR DALAM MENDUKUNG TARGET SDGS 4 (PENDIDIKAN BERKUALITAS) - H Priyono Tri Febrianto; Siti Maisaroh; Arvita Indah Wulandari; Arina Hevy Alifiyah; Qurrotul Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the influence of YouTube-based learning media on elementary school students’ motivation in Social Studies learning and its role in supporting the achievement of Sustainable Development Goals (SDGs) 4, particularly quality education. The problem addressed in this research is the low learning motivation caused by conventional teaching methods that are less engaging for digital-native students. The objective of this study is to analyze how YouTube videos as learning media can enhance students’ motivation and contribute to improving the quality of education. This research employs a qualitative descriptive approach using library research methodology, which involves analyzing relevant literature such as books, journal articles, and online sources. The findings indicate that YouTube-based learning media significantly improve students’ motivation by increasing their interest, attention, and active participation through audio-visual content. Additionally, the use of video media helps present abstract Social Studies material in a more concrete and understandable way. Furthermore, integrating YouTube into the learning process supports the development of 21st-century skills and promotes more innovative, flexible, and meaningful learning experiences. Therefore, YouTube-based learning media can serve as an effective alternative to enhance learning motivation and contribute to achieving quality education in line with SDGs 4.